Designing Audiolingual Learning Model Using the Self-Record Method as A Medium and it’s Impact to Student Listening and Speaking Ability at SMP Negeri 4 Tanjung Morawa - Wulandari, Cynthia; Harianto II; Asnawi (International Journal of Educational Research Excellence (IJERE), 2025)
In the concept of language mastery, the stages to be passed are: (1) listening, (2) understanding the meaning of speech, (3) practicing/repeating speech, (4) reading, (5) writing. To achieve fluency in English, students must master all four of these abilities. One solution is for students to listen to their own conversations, which will make it easier for them to gain experience in listening to English conversations. Self-recording video is a practice where students or study participants use technological devices like smartphones, phones, or laptops to record themselves speaking in the target language, usually English, either inside or outside the classroom. This Research was aimed to made a design of Self-Recording Video as a method to improve student’s listening and speaking abilities. The sample of this research was students in class 9A and 9B. The study collected data by applying the following techniques: study literacy, interview, observation, test, and documentation. In developing of learning material by using SRV method several process criteria were used R&D cycle of Borg and Gill. The result of this research was showed that Implementing Self-record is significant to increase Student English language listening and speaking abilities at SMP NEGRI 4 TANJUNG MORAWA by increase the students listening skill by 23.22 points and the T-test score was 0,03, and the speaking skill by 22,61 point, and the T-test score was 0,01. The learning design of Self-record learning models is in the good levels to implementing at SMP NEGRI 4 TANJUNG MORAWA, by the design evaluated score was 3.51, indicating that the research design developed by the researcher was considered to be of "good" quality.